The study on ODL mentoring program in assisting the repeater students for civil engineering courses / N. Aishah Abdul Rahman … [et al.] - Abdul Rahman, N. Aishah; Mokhtar, Hamizah; Muhamad, Noor Safwan; Ismail, Muhammad Isha (Universiti Teknologi MARA, Pahang, 2022)
The Open and Distance Learning (ODL) platform as an extended classroom without regular face-to-face contact between educators and students has significantly impacted students' performance. With no real face-to-face interaction and consultation, ODL classes can be challenging to students. This is even more prevalent among repeaters who are normally considered as weak students. Therefore, there is a need for a virtual mentoring project to assist the repeaters during ODL season. This study is to observe the students’ performance feedback from repeater students for civil engineering courses through the ODL mentoring program. The questionnaires obtained from the program were analyzed to achieve this objective. The analysis shows that all respondents agreed that online mentoring program enhanced their understanding of the topics which resulted into 86% of them, 12 out of 14 repeater students passed the course. The success of the ODL mentoring program in assisting repeater students was presented in detail. The findings can help educators develop strategies to assist repeater students to meet the expectations and requirements of the courses taken. Advancements of enhanced strategies would help improve the success of implementing the ODL mentoring program for repeater students from stopping repeating the course more than once.